China: Understanding a new global economic player - Horst Siebert (Kiel Institute for the World Economy (IfW), 2006)
This paper analyzes China's economic performance in the last 25 years and discusses its prospect for growth in the future. China has enjoyed high annual GDP growth rates of about ten percent in the last 25 years. Exports and investment were the two driving forces of the growth process. FDI plays an important role. However, property rights, a crucial element in transforming a communist society, are far from being clearly developed. Structural issues such as the state-owned firms and the loss-making of the banking industry have to be solved. Monetary policy is complicated by the accumulation of reserves. Major policy issues in the future include the institutional deficit, especially with respect to the rule of law and the lack of democracy.
Keywords: K; E2; E4; F10; F43; 330; FDI; Developing countries; Transformation; Exchange rate policy; Property rights; Future scenarios; Growth process; Wirtschaftswachstum; Exportinduziertes Wachstum; Direktinvestition; Investition; Eigentumsrecht; Wirtschaftspolitik; Wechselkurspolitik; Systemtransformation; China